Edible Coating Starch Making for Preserving Fruit as an Alternative for Junior High School Science Practicum on Additives Substance Material - Diah Puji Lestari; Insih Wilujeng (Pendidikan Kimia Unimus, 2022)
This research aimed to study the edible coating starch making for preserving fruit as an alternative for junior high school science practicum on additives substance material. The edible coating is a thin layer that can be consumed, inhibits microbial growth, and provides physical protection to the coated fruit. The steps to make edible coating starch carried out by the researchers are as follows: producing an eatable coating solution from cassava starch, making citronella extract fragrant, and application on fruit. Based on the results of research, edible coating starch with the addition of 30% citronella grass extract was the best treatment. Grapes could last up to 14 days of storage and showed a decrease in water content and fruit sugar by 72.22% and 4.80%, respectively. Based on the questionnaire of the teacher's responses to the manufacture of edible coating starch as an alternative to the science practicum, the results on the material aspects were in the marvelous category (90.62%), practical aspects were in a good category (79.01%), the cost and safety aspects were in the good category (85.11%). Therefore, it was possible to apply edible coating practice in schools.